The Influence of Work Environment, Motivation and Discipline on Employee Loyalty in Sza Sukoharjo Convection - Andi Wibowo; Istiatin Istiatin; Ratna Damayanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to determine the effect of work environment, motivation, and discipline on employee loyalty at Konveksi SZA Sukoharjo. This study employs a quantitative descriptive method. The population and sample in this study consisted of all 40 employees of Konveksi SZA, selected using the census technique. Data collection techniques included questionnaires, observations, and documentation. The data analysis techniques include validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and the coefficient of determination. The results indicate that the work environment, motivation, and discipline have a positive and significant effect on employee loyalty, both partially and simultaneously. The coefficient of determination (Adjusted R Square) of 0.897 indicates that 89.7% of the loyalty variable can be explained by these three independent variables.